Study of Trichinella spp. Seroprevalence in Horse Population of West Azerbaijan, Northwestern Iran - Zanyar Pirkani; Arash Araghi-Sooreh; Fateme Kamalinejad (Iranian Journal of Parasitology)
Background: We aimed to determine the seroprevalence of Trichinella in horses in West Azerbaijan Province, Iran a region known for its wildlife interactions. Methods: The study was conducted in March 2016 across four cities in West Azerbaijan: Urmia, Chaldoran, Sardasht, and Khoy, Iran. A total of 184 equines, ranging from three to over ten years of age, were randomly sampled. Blood samples were collected and were analyzed using the ID Screen® Trichinella Indirect Multi-species ELISA to detect antibodies. Results: Of the 184 serum samples, 4 (4.3%) from northern counties and 2 (2.2%) from southern counties tested positive for trichinellosis. Chi-square and Fisher's exact tests indicated no significant correlations between age, gender, or residential location and disease prevalence. The logistic regression model was not statistically significant (P = 0.754), revealing that these demographic factors do not substantially influence trichinellosis risk in the studied equines. Conclusion: This study provides crucial insights into the low seroprevalence of Trichinella in horses in West Azerbaijan, suggesting that equines may not be primary reservoirs of the parasite despite overlapping habitats with infected wildlife.